2017
DOI: 10.1371/journal.pone.0181779
|View full text |Cite
|
Sign up to set email alerts
|

Microwave & magnetic proteomics of macrophages from patients with HIV-associated cognitive impairment

Abstract: ObjectiveHIV-infected monocytes can infiltrate the blood brain barrier as differentiated macrophages to the central nervous system, becoming the primary source of viral and cellular neurotoxins. The final outcome is HIV-associated cognitive impairment (HACI), which remain prevalent today, possibly due to the longer life-span of the patients treated with combined anti-retroviral therapy. Our main goal was to characterize the proteome of monocyte-derived macrophages (MDM) from HACI patients, and its association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…However, this is the first study suggesting that HIV-1 infection in macrophages promotes lysosomal exocytosis and that it is attenuated by JWH-133 treatment, which is a significant advance for future treatment modalities. In a previous TMT-based proteomics study, we observed an increased CATB expression in macrophages from HIV-seropositive women with impaired cognition compared to asymptomatically impaired HIV-seropositive woman after 7 days in culture, suggesting that CATB protein expression is linked to cognitive impairment in HIV-seropositive women [ 96 ]. In this study, we found that intracellular CATB levels were increased by HIV-1 infection and decreased by JWH-133 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first study suggesting that HIV-1 infection in macrophages promotes lysosomal exocytosis and that it is attenuated by JWH-133 treatment, which is a significant advance for future treatment modalities. In a previous TMT-based proteomics study, we observed an increased CATB expression in macrophages from HIV-seropositive women with impaired cognition compared to asymptomatically impaired HIV-seropositive woman after 7 days in culture, suggesting that CATB protein expression is linked to cognitive impairment in HIV-seropositive women [ 96 ]. In this study, we found that intracellular CATB levels were increased by HIV-1 infection and decreased by JWH-133 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MOR increased expression of MICOS subunit MIC26 and Sorting and assembly machinery component 50 homolog (SAMM50), which maintain cristae morphology essential for proper ETC function and shunting of metabolites (Figure S3). 73,74 Other potential sources of increased ROS include phagocyte oxidative bursts and reduced ROS neutralization 21,75 …”
Section: Discussionmentioning
confidence: 99%
“…73,74 Other potential sources of increased ROS include phagocyte oxidative bursts and reduced ROS neutralization. 21,75 MOR significantly increased expression of CD38, a key enzyme that creates nicotinic acid adenine dinucleotide phosphate using NAD + (Figure 4A). This is implicated in metabolic aging since cells continuously need NAD + reserves to support glycolysis and the citric acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that HIV-infected women with cognitive impairment have higher levels of soluble insulin receptor (sIR) in plasma and cerebrospinal fluid (CSF), when compared to HIV-negative women, as well as lower levels of insulin receptor substrate 1 (IRS-1) tyrosine phosphorylation in plasma ( 13 15 ). Metabolic enzymes are also altered in patients with HAND ( 16 , 17 ). The mechanisms responsible for the secretion of the full-length sIR to the plasma of HIV-infected women with HAND remain unknown.…”
Section: Introductionmentioning
confidence: 99%